Mengungkap Dampak Trilogi Kepemimpinan, Motivasi Dan Kompensasi Terhadap Kepuasan Kerja Pegawai Dinas Kesehatan Kota Balikpapan - Husniah, Husniah; Hadiyatno, Didik; Cahyaning Putri Cipto, Rahajeng (Jurnal GeoEkonomi, 2026)
This research was aimed to analyze the influence of leadership, motivation and compensation impact employee job satisfaction at the Balikpapan City health Office. This research was carried out within the Balikpapan City Health Office with the involvement of 80 respondents. The research method used was quantitative, whare data was gathered through questionnaires distributed to 80 ASN employees at the Balikpapan City Health Office. In this study, the sampling method employed was a total sample, meaning the entire ASN population was included as respondents. Data analysis was performed using multiple linear regression via the Partial Least Square (PLS) program. The findings revealed that leadership did not significantly influence job satisfaction on its own. However, the motivation variable showed a significant positive influence on job satisfaction, as well as the compensation variable which also had a significant positive effect on job satisfaction.